APOPTOSIS MEDIATED ANTI-PROLIFERATIVE ACTIVITY OF KAEMPFEROL AND QUERCETINE ISOLATED FROM THE LEAVES OF ALTINGIA EXCELSA AGAINST HUMAN TONGUE SP-C1 CELL LINES - risyandi anwar; arlette suzy setiawan; Supriatno Supriatno; Unang Supratman (Universitas Baiturrahmah, 2021)
Introduction: The leaves of Altingia excelsa were found to strongly inhibit SP-C1 human tongue cancer cell lines. This study was focused on identifying antiproliferative compounds found in A. excelsa leaves and assesment their action mechanism. Methods: Extracts of Methanol A. excelsa were fractionated based on their solvent polarity using n-hexane, ethyl acetate, and water. The anti-proliferative testing were tested in vitro against SP-C1 human tongue cancer cell lines using the MTT assay. Isolated the active compound used column chromatography and identified by the spectroscopic method. The isolated compound was also tested for its anti-proliferative testing and ELIZA method of apoptotic induction. Results: This work resulted in the isolation of a flavonoid, which was identified to be kaempferol and quercetin. The compound inhibited SP-C1 proliferation of cell in a time- and dosedependent manner with IC50 values of 0.72 µg/mL and 0. 70 µg/mL for the 24 hours treatments, respectively. Furthermore, promoting apoptosis via the intrinsic pathway, thereby increasing the activity of caspase-8 and caspase-9. Conclusions: These results suggest that kaempferol and quercetin the anticancer compound found in A, excelsa provided a basic for its potential use in cancer disease treatment management